Human papillomavirus genotypes in genital warts in Latin America: a cross-sectional study in Bogota, Colombia. (July 2013) - Hernandez-Suarez, G; Pineros, M; Vargas, J C; Orjuela, L; Hernandez, F; Peroza, C; Torres, D; Escobar, A; Perez, G
Summary: Epidemiological studies on benign lesions related to human papillomavirus (HPV) infection are scarce in Latin America. We enrolled 342 consecutive patients with lesions suspected of being genital warts (GW). All patients underwent confirmatory biopsy and GP5+/GP6+/− Reverse Line Blot HPV testing on frozen tissue. In 261 (81%) cases, the diagnosis was confirmed by histopathology and HPV was detected in 90.6% of men and 87.7% of women. HPV 6 was by far the most common type in both women (62%) and men (56%), followed by HPV 11 (∼20%). Co-infection with these two types occurred in 7% and 12% of women and men, respectively. HPV16 ranked third in prevalence, with 16% of patients testing positive. Twenty-five percent of cases tested positive for multiple HPV genotypes. Although HPV 6 and HPV 11 were the main types detected and no differences between men and women were observed, we found HPV 11 contributed more to GW aetiology compared with previous reports, showing a variability of HPV type distribution in GW across populations. This information is valuable baseline data in Latin America for future estimations of the burden of GW in men and women and shows the potential benefit obtainable by prophylactic vaccination against HPV types 6 and 11.